STUDI EKSPERIMENTAL FALLING FILM EVAPORATOR PADA EVAPORASI NIRA KENTAL - Fitri, Medya Ayunda; Suhadi, Suhadi; Altway, Ali; Susianto, Susianto (Universitas Nahdlatul Ulama Sidoarjo, 2016)
Falling film evaporator is a constructed equipment for concentrating dilute solution that are sensitive to heat flowing form a thin film. This research aims to study the evaporation of cane juice concentrated with air flow on falling film evaporator and knowing evaporation rate occured in falling film evaporator used. In the process, cane juice from plant pumped to the falling film evaporator that used in this experiment. This research used concentrated cane juice and air flow rate for variables of this experiment. Cane juice flow from top of evaporator through distributor to form thin film and air flow from the bottom of evaporator. After that, temperatur of pipe wall, inlet and outlet temperature of cane juice and air were measured. This experiment concluded that the highest concentration of outlet solution is 59 brix for liquid flow rate 154 l/h and air flow rate 10 m3/h, and the other hand inlet solution concentration 51 brix. Optimum evaporation rate is 35 kg/m2.h for 51 brix and air flow rate 10 m3/h.